Influence of constructed rapid infiltration system on groundwater recharge and quality - Guo, Chao; Li, Jiake; Sun, Yingying; Gao, Wang; Mao, Zhongan; Ye, Shenglan (Frontiers in Environmental Science, 2022)
Infiltration of stormwater through green surfaces is an important means of groundwater recharge. However, the increase in constructed impervious area caused by intensive urbanization has led to a reduction in rainwater infiltration over the past decade. The constructed rapid infiltration system (CRIS) with an ample open space plays an important role in groundwater recharge. This study aims to explore the influence of stormwater (roof runoff) concentration infiltration on groundwater table and quality in the CRIS. Groundwater table monitoring is conducted for more than 2 years (October 2017–December 2019) by continuous online monitoring combined with manual sampling. Results show that the addition of zeolite to the CRIS has good removal effect on rainfall runoff pollutants, and the influence of stormwater concentration infiltration on groundwater quality is small when the CRIS enters the stable running stage. The increased proportion of chemical oxygen demand, N, and P in J1 are all less than 10% from 2018 to 2019, and they are less than 20% for heavy metals. The stormwater concentration infiltration can recharge groundwater and increase the groundwater depth, and the groundwater depth varies from 0.5 m to 1.5 m during the monitoring period. The influence scope of the concentrated infiltration on groundwater table and quality is between 25 and 45 m. The response of the groundwater table and quality to the stormwater concentration infiltration of J1, 25 m away from the CRIS, exhibits hysteresis, and the lag time is about 3–4 months. Conclusions from relevant research can provide important theoretical support for the further study of groundwater recharge by the CRIS.